Relationship between buyer and supplier in outsourcing of information technology services - Martins, A.; Duarte, H.; Costa, D. (22nd International Symposium on Logistics, 2017)
Companies rely on others to achieve its goals. This is not only true in terms of management of the flows of information and materials through the supply chain but also in terms of performing specific processes and sub-processes intimately related to the company’s operation. IT Outsourcing (ITO) is increasing worldwide and the relational governance impacts the outsourcing outcomes (Lacity et al, 2016). This perspective is usually visited for the buyer and supplier perspectives using decision makers and leaving a gap in literature in terms of the perspective of the consultants. This paper aims at analysing, in ITO, how the development of the relationship between buyer and supplier strengthens supplier performance over time, from the perspective of the consultants. A survey to IT consultants was applied and then a multilevel analysis was performed, taking account for the aggregate values of the variables characterizing buyer supplier relationships based on Johnston and Staughton (2009), Krause et al. (2007) and Blonska et al. (2013). Findings show that strategic relationships are associated with higher supplier investment in relational management. In this type of relationship higher levels of trust are linked to an attribution of more recognised benefits from the relationship, and reciprocal investment to the buyer. Furthermore, an improvement of the dedication in the relation and an improved service performance were attributed by IT consultants to the supplier.